Komparasi Penggunaan Strategi Scramble Dengan WordSquare Terhadap Hasil Belajar IPA Kelas V - Saputri, Fitria Isty Gita (2016)
This research aims to know 1) there are diffrent between scramble strategy and word square strategy to the result of learning science at the fifth grade students of SD Muhammadiyah 3 Nusukan Surakarta,20 which bigger effect are between scramble strategy and word square strategy to the result of learning science at the fifth grade students of SD Muhammadiyah 3 Nusukan Surakarta. This reseacrch is experiment. The population of research is the fifth grade students of SD Muhammadiyah 3 Nusukan Surakarta. Technique of collecting data is used test,observation and documentation. Technique of analyzing data is used T experiment before the experiment of prerequisite analyzing is normality experiment homogeity. Base the result of analyzing data with signification standart 5 % gets result t arithmatic > t tabel , there are 2,251 > 1,997 with the average of result learning science at the fifth grade students of SD Muhammadiyah 3 Nusukan Surakarta is 77,58 > 70,19. The conclusion of research is as 1) there are diffrentiation betwen diffrent between scramble strategy and word square strategy to the result of learning science at the fifth grade students of SD Muhammadiyah 3 Nusukan Surakarta in 2015/2016 academic year. scramble strategy is bigger effect to increase science than Word Squere strategy at the fifth grade students of SD Muhammadiyah 3 Nusukan Surakarta 2015/2016 academic year. Key Word: scramble strategy, word square strategy, the result of learning science